Creating Critical Distance: Pierre Batiffol and Alfred Loisy on the Church. Issue 1 (January 2019) - Talar, CJT
Alfred Loisy's L'Évangile et l'Église (1902), followed by his even more controversial Autour d'un petit livre (1903), brought into the open tensions that had been festering within the Catholic biblical movement over the preceding years. "Progressives" such as Lagrange and his close ally Pierre Batiffol had, on one hand, to defend in principle a legitimate use of criticism, and on the other to distinguish that use from the corrosive effects of its employ by Loisy. Divergent approaches to the use of criticism and its relation to theology surfaced in their respective approaches to the kingdom of God in the preaching and teaching of Jesus, and the Church that developed out of his ministry. Given the centrality of ecclesiology at Vatican II, the question of that relationship resurfaced, albeit on a different footing and possibilities for resolution.